Development of spectrophotometric method for the analysis of paraformaldehyde in commercial and industrial disinfectants - Fagnani, E.; Melios, C. B.; Pezza, L.; Pezza, H. R. (Editora Unesp, 2002)
This paper describes a spectrophotometric method for the paraformaldehyde analysis in industrial and commercial disinfectant samples using chromotropic acid, concentrated hydrochloridric acid and hydrogen peroxide. The reaction produces a violet-red compound (lambda(max) = 575 nm). The method permits the determination of paraformaldehyde over a concentration range of 0.8-4.8 mg L-1 and the results obtained by the proposed method compared very favorably with those obtained by NIOSH's standard procedure.
Keywords: disinfectant analysis; formaldehyde quantification; spectrophotometry; chromotropic acid